Is it price a key factor that determined by consumers in buying car? A case study: Kota Bharu / Nor Hazirah Jaya Mara - Jaya Mara, Nor Hazirah (2011)
Nowadays, people are more demanding about what they want. When buying a car, consumers can make use of 3 senses which are vision, hearing and touch. The customers who had visited the showroom believed that the look of the vehicle is extremely important since it defines their personality. Therefore, this study investigates on what factor that influence customers’ buying behaviour towards automobile product. A total of 100 respondents were selected randomly in this study. The respondents are customers of Aman Razak Group. From this study, we can know the factor that most influence customers on their buying decision. This research has shown that quality is the most important factor that influences customers’ buying behaviour towards car. But, the other independent variables for service package, price and brand do not influence consumers’ buying behaviour towards car due to the significant value is more than the degree of the significant value. Finally this study offers information that useful to the industrial players in order to develop their strategic marketing planning. These strategic recommendations were listed in the last chapter of this thesis